DIPG-03. THERAPEUTIC TARGETING OF TRANSCRIPTIONAL ELONGATION IN DIFFUSE INTRINSIC PONTINE GLIOMA. (4th December 2020) - Katagi, Hiroaki; Takata, Nozomu; Aoi, Yuki; Zhang, Yongzhan; Rendleman, Emily J; Blyth, Gavin T; Eckerdt, Frank D; Tomita, Yusuke; Sasaki, Takahiro; Saratsis, Amanda M; Kondo, Akihide; Goldman, Stewart; et al.
Abstract: Diffuse intrinsic pontine glioma (DIPG) is highly aggressive brain stem tumor and needed to develop novel therapeutic agents for the treatment. The super elongation complex (SEC) is essential for transcription elongation through release of RNA polymerase II (Pol II). We found that AFF4, a scaffold protein of the SEC, is required for the growth of H3K27M-mutant DIPG cells. In addition, the small molecule SEC inhibitor, KL-1, increased promoter-proximal pausing of Pol II, and reduced transcription elongation, resulting in down-regulate cell cycle, transcription and DNA repair genes. KL-1 treatment decreased cell growth and increased apoptosis in H3K27M-mutant DIPG cells, and prolonged animal survival in our human H3K27M-mutant DIPG xenograft model. Our results demonstrate that the SEC disruption by KL-1 is a novel therapeutic strategy for H3K27M-mutant DIPG.